2016
DOI: 10.1111/vco.12226
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of advanced canine anal sac adenocarcinoma with hypofractionated radiation therapy: 77 cases (1999–2013)

Abstract: Currently no standard of care exists for advanced, inoperable or metastatic anal sac adenocarcinoma (ASAC). The objective of this retrospective study was to assess the role of hypofractionated radiation therapy (RT) in 77 dogs with measurable ASAC. A total of 38% of dogs experienced a partial response to RT. For dogs presenting with clinical signs related to the tumour, improvement or resolution of signs was noted in 63%. For dogs presenting with hypercalcemia of malignancy, resolution was noted in 31% with RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 20 publications
2
52
0
2
Order By: Relevance
“…Similar to previous publications, several clinical variables were related to the outcome in univariate analyses in our study. The presence of clinical signs associated with the tumour, the size of the primary tumour and the presence of nodal metastasis were significantly associated with PFI and OS, whereas hypercalcaemia was significantly associated with OS only. The presence of clinical signs associated with the tumour could reflect increasing size of the primary tumour and metastatic disease within lymph nodes as well as the presence of hypercalcaemia.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similar to previous publications, several clinical variables were related to the outcome in univariate analyses in our study. The presence of clinical signs associated with the tumour, the size of the primary tumour and the presence of nodal metastasis were significantly associated with PFI and OS, whereas hypercalcaemia was significantly associated with OS only. The presence of clinical signs associated with the tumour could reflect increasing size of the primary tumour and metastatic disease within lymph nodes as well as the presence of hypercalcaemia.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, several factors have been identified as negative prognosticators for dogs with ASGAC, including increasing primary tumour size, presence of lymph node metastasis, presence of distant metastasis and lack of therapy . The prognostic influence of hypercalcaemia (reported to occur in 16%‐53% of the cases) remains controversial, with some studies showing significantly decreased survival with hypercalcaemia, while others found no predictive value …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations